Protective Effects of Aspirin Supplemented With Quercetin in L-NAME-Induced Preeclampsia-Like Rats - Ding, J; Yang, S; Chen, D; Shi, X; Zhang, Y; Song, L; Zhang, J (Physiological research, 2024)
Aspirin supplemented with quercetin was reported to enhance the therapeutic effects of aspirin in a rat model of preeclampsia. In this study, the underlying mechanisms were further explored. Preeclampsia was induced by L-NAME (50 mg/kg/day) via oral gavage from gestation day (GD)14 to GD19. Aspirin (1.5 mg/kg/day) administration was performed using aspirin mixed with rodent dough from GD0 to GD19. The administration of quercetin (2 mg/kg/day) was performed by intraperitoneal infusion from GD0 to GD19. Protein levels were evaluated using ELISA or Western blot, and microRNA (miRNA) level was evaluated by RT-PCR. Aspirin supplemented with quercetin ameliorated the increase of systolic blood pressure (SBP), proteinuria, tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6) levels, and improved the pregnancy outcomes in preeclampsia rats. Aspirin supplemented with quercetin inhibited miR-155 expression in preeclampsia rats. The decreased miR-155 level in placenta further increased the protein level of SOCS1 and inhibited the phosphorylation of p65. In this study, we demonstrated that aspirin supplemented with quercetin enhanced the effects of aspirin for the treatment of preeclampsia.
Keywords: Animals; preeklampsie; quercetin; Female; ženské pohlaví; Aspirin; Placenta; lidé; těhotenství; NG-Nitroarginine Methyl Ester; NG-nitroargininmethylester; Pre-Eclampsia; mikro RNA; krysa rodu Rattus; MicroRNAs; Quercetin; zvířata; Pregnancy; placenta; Rats; Humans